PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 27 PADANG TAHUN PELAJARAN 2012/2013 - Tuti, Desi Surya; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2013)
This research is based on the students comprehension of mathematical concepts are still low. This study aims to determine: 1) how the development indicators of students comprehension of mathematical concepts by applying active learning strategies The Power Of Two types accompanied quiz; 2) whether students comprehension of mathematical concepts by applying active learning strategies The Power Of Two types of quizzes with better than students comprehension of mathematical concepts with conventional learning in class VIII SMP 27 Padang. Type of research is experimental research with the design random on the subject. Population in this research is student class VIII SMPN 27 Padang. Sample is done randomly. The instrument of this research is quizzes and final test. Quizzes Analysis technique used techniques percentage and final test data analysis techniques using the t test. Results were obtained: 1) indicators of achievement of students comprehension of mathematical concepts are not stable or up and down, 2) hypothesis testing results obtained tvalue=2,37Â  is greater than ttable=1,645. It can be concluded that the students comprehension of mathematical concepts by applying active learning strategies The Power Of Two types of quizzes with better than students comprehension of mathematical concepts with conventional learning at the level of 95% in SMP 27 Padang.